Dual‐Enhanced SERS Satellite Immuno‐Nanocomplex for Multiple PSA‐Mediated PHI Assay Toward Clinical Prostate Cancer Screening - Chen, Dong; Ma, Yilin; Yang, Annan; Hu, Liping; Zhou, Hanlin; Xu, Jun; Chen, Shanze; Nie, Dingmeng; Feng, Weifeng; Cai, Huaihong; Cong, Yanguang; Pi, Jiang; et al. (Advanced science, 2025)
Prostate specific antigen (PSA) is widely used in liquid biopsy of prostate cancer (PCa) but still faces challenges due to the poor specificity. Herein, this study reports a double‐SERS satellite immunoassay, made of an Au–Ag dealloyed intra‐nanogap nanoflower (Au–Ag DINF) with strong SERS signals and Au magnetic nanoparticles (AuMNPs) with magnetic capture and SERS amplification, for sensing multiple PSA (free PSA (fPSA), complexed PSA (cPSA) and [‐2]proPSA (p2PSA)) toward potential PCa screening. Unlike the previous studies focus on the tPSA and fPSA/tPSA ratio (f/t PSA%), this work introduces a multiple PSA‐mediated Prostate Health Index (PHI) assay with significantly increased the predictive accuracy and specificity of PCa, especially the patients with a tPSA level in the “diagnostic gray zone”. Practical analysis of clinical samples demonstrated the SERS immunoassay is capable of identifying the PCa subjects from healthy candidates (N = 13), and monitoring PCa patients before and after surgery (N = 5), as well as screening suspicious ones who are in the “gray zone” (N = 10). Overall, benefiting from the PSA‐responsive satellite immuno‐nanoassemble strategy, dual‐SERS magnification effect, and multiple PSA‐based PHI assessment, this proposes bioassay held enormous potential for the early diagnosis, screening, monitoring, and prognosis of PCa. This study reports a double‐SERS satellite nanocomplex immunoassay that made of an Au–Ag dealloyed intra‐nanogap nanoflower (Au–Ag DINF) and Au magnetic nanoparticles (AuMNPs) for multicomponent PSA, and introduces a prostate Health index (PHI) assay for potential PCa screening, especially the patients with a tPSA level in “diagnostic gray zone”.